Tourism at Crossroads Between the Prospects and Challenges of the Fourth Industrial Revolution: Literature Review - Yasin, Abdi Shukri; Gedecho, Kibru Alemu (Acta Carolus Robertus, 2024)
The Fourth Industrial Revolution (4IR) is reshaping the landscape of the tourism industry, presenting both unprecedented opportunities and complex challenges. This study explores the prospects and challenges posed by 4IR for tourism through a literature review. The objective is to provide a comprehensive understanding of the interplay between technological advancements and the tourism sector. Employing a rigorous methodology, peer-reviewed academic articles, conference papers, and relevant book chapters were analyzed, focusing on key technologies such as artificial intelligence, the Internet of Things, robotics, and big data. The results highlight promising prospects, including enhanced customer experience, smart destinations, augmented and virtual reality, data-driven decision making, sustainable tourism practices and increased efficiency and productivity alongside challenges like data security and privacy concerns, digital divide, job displacement, overreliance on technology, ethical considerations and infrastructure and investment. The paper's key contribution lies in it’s provision of categorical perspective of the various impacts of 4IR on tourism. Also, the study provides valuable insights for stakeholders, policymakers, and industry players to navigate the transformative era of the Fourth Industrial Revolution in the tourism sector. Moreover, the study identified gaps in existing literature and provides direction for future works.
Keywords: Fourth Industrial Revolution; tourism industry; technological advancements; prospects; challenges; literature review